(3OjhGf SYOGdOjf Hf YQHjs - (3eMeO Hf eMeO Hf Ydj Hf YQHj GdWGFj GdMGJej, SYO GdOjf , J (B656 (3g` s
(3ChdgG (B:s
(3bGd GdTjN SYOGdOjf GdWGFj GdMGJej QMefG Gddg Hg dGe GdYPhd Ydi ghGg hafOG aCYGO HGddhe GdZQGe ceG HOG s
(3BNQgG (B:s
(3BjG Cj gPG GdaGVd GdeJaVd BjGOjc HGdeYQha Chdi hChd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3Ydi ghGeTgG JYdjbGJ hCTYGQ cKjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B118 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B508s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(11156 (3R(B) s
Keywords: (3GdCOHs